Kompetencje kluczowe w rozwoju przyszłej kariery zawodowej pokolenia Z a edukacja - Katarzyna Jagielska (Edukacja Ustawiczna Dorosłych, 2023)
Today's labour market is governed by uncertainty and randomness. It is difficult to predict how the demand for workers in particular industries will change and what competences will be required of employees. Current reports indicate that only 10 per cent of people have an occupation that will not change, 20 per cent have an occupation that will disappear and 70 per cent will need to retrain. One of the competences of the future will therefore be the competence of lifelong learning. The ability to analyse data, creativity, critical thinking, stress management and others will also be necessary. This article presents the example of the Catholic Montessori Secondary School in Kraków which prepares students to function freely on the labour market. The research was conducted in a qualitative paradigm between 2020 and 2022. The case study method was used. The aim of the research was to identify whether the school's working methods are related to the development of key competences necessary in the contemporary labour market. The main research problem was centred around the question of which working methods used at the school are most effective in shaping those competences? The analysis presents the school's concept of work in relation to the formation of competences of the future.